100 most beautiful cathedrals of the world . a journey across five continents - leier , manfred .; manfred leier . (england : reo international .)
a journey through five continents.
europe /asia / africa / america / australia .
All age.
Keywords: Cathedrals -- Guidebooks. .; Cathedrals -- History -- Guidebooks. .